PECULIARITIES OF CLINIC AND COURSE OF VIBRATION DISEASE IN THE VIBRATION EXPOSURED MINERS OF KUZBASS REGION - L. N. Shpagina; V. V. Zakharenkov; S. N. Filimonov (Acta Biomedica Scientifica, 2012)
Clinical manifestations of vibration pathology with different degree of pathological process intensity were studied in 288 vibration exposured miners. Peculiarities of formation of vibration pathology in Kuzbass miners are connected with the development of angiodystonic syndrome (97—100 %) with acrospasm attacks. Formation. of vibration pathology is associated with the increase of arterial hypertension incidence — up to 28,3 % at stage I and up to 34,1 % at stage II, that is possibly caused by the increase of endothelia system dysfunction. There is progressive disease course both in the persons continuing contact with vibration and in those who stopped it.